Financial Management in Government: Insights on Skills Development - Beazley, Ivor (OECD Publishing, 2019)
Financial management is a critical capability for governments, enabling them to deliver on their priorities and fulfil promises made to parliament and citizens. Skilled human resources are the foundation of these capabilities. The Organisation for Economic Cooperation and Development's (OECD) "Skills for a high performing civil service" framework identifies professional expertise as one of the three core skill areas that drive public value, together with strategic orientation and innovation. The task of providing the civil service with the right skills to carry out financial management functions has however become more challenging